Integrated system of phytodepuration for agro-industrial waste water –An eco friendly technology - Bhardwaj, Namita (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The integrated system of phytodepuration (ISP) is a biotechnology based on the combination of phytodepuration in pluriculture and conventional depuration (sewage treatment) technology .It is different from other conventional phytodepurative system in this technology chemical products such as flocculants and disinfectants not required and due to no sludge production it is an ecofriendly technology which is safer to environment.